Improving Tax Compliance Risk Management of Large Businesses in Vietnam - Thi Cam Giang Nguyen; Thi Thanh Hoai Nguyen (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Tax compliance risk management is a modern management method to improve the compliance of taxpayers in general and large enterprises in particular. Over the past 10 years, tax compliance of large enterprises has become a significantly concerned issue of policymakers and tax administrators over the world. Due to the goal of profit maximization, the complex nature of business operations and spread across many regions and countries, large enterprises, especially multinational corporations, are at the high risk rate of tax compliance. The article uses a set of compliance risk assessment criteria of enterprises and secondary data from 556 large enterprises in Vietnam to assess the level of risk, classified by economic sector and type of business. The results show that the foreign-invested economic sector and the type of limited liability company with 2 or more members have the highest level of compliance risk while the state sector and the 100% State owned enterprises have the lowest risk. Therefore, it recommends that improving tax compliance and reforming tax incentive policies, especially for FDI enterprises are of necessity.